The UF Deep Brain Stimulation Cognitive Rating Scale (DBS-CRS): Clinical Decision Making, Validity, and Outcomes - Kenney, Lauren; Rohl, Brittany; Lopez, Francesca V.; Lafo, Jacob A.; Jacobson, Charles; Okun, Michael S.; Foote, Kelly D.; Bowers, Dawn (Frontiers in Human Neuroscience, 2020)
To more efficiently communicate the results of neuropsychological assessment to interdisciplinary teams, the University of Florida Neuropsychology Service developed a Deep Brain Stimulation-Cognitive Rating Scale (DBS-CRS). This tool condensed results of a 3-hour exam into a 5-point scale ranging from 1(least) to 5(most) cognitive concern for DBS surgery. In this study, we evaluated the role of the DBS-CRS in clinical decisions by the interdisciplinary team to proceed to surgery, its relationship to objective neuropsychological scores, and its predictive utility for clinical outcome. We retrospectively examined 189 patients with Parkinson disease who were evaluated for DBS candidacy (mean age 64.8 [SD 9.2], disease duration 8.9 years [SD 5.0], UPDRS-Part III off medication 38.5 [SD 10.5], Dementia Rating Scale-II 135.4 [SD 6.0]). Approximately 19% of patients did not proceed to surgery, with neuropsychological red flags being the most commonly documented reason (57%). Patients who underwent DBS surgery had significantly better DBS-CRS scores than those who did not (p<0.001). The two strongest and unique neuropsychological contributors to DBS-CRS ratings were delayed memory and executive function, followed by language and visuoperception, based on hierarchical linear regression that accounted for 77.2% of the variance. In terms of outcome, DBS-CRS scores were associated with higher quality of life, less severe motor symptoms, and better daily functioning six months following DBS surgery. Together, these findings support the construct and predictive validity of the DBS-CRS as a concise tool for effectively communicating pre-DBS cognitive concerns to an interdisciplinary team, thereby aiding decision making in potential DBS candidates.